Obesity and glycated hemoglobin: is there a relation with oxygen saturation in type 2 diabetes mellitus? - Chouhan, Nusrat; Manhas, Monica; Kotwal, Suman; Majid, Mohsina; ., Mrityunjay (International Journal of Research in Medical Sciences, 2022)
Background: Diabetics and obese persons are highly susceptible to cardiovascular diseases (CVD). Obesity causes hypoxemia and glycated hemoglobin (HbA1c) also is known to lower the oxygen-carrying capacity and related systemic vascular vasodilatory adaptations and responses. Aim was to assess the effect of obesity and glycosylated hemoglobin on oxygen saturation in patients of type 2 diabetes mellitus (T2DM). Methods: HbA1c level and oxygen saturation (SpO2) were measured in 100 adult, obese (Body mass index>30) T2DM patients. Results: Mean HbA1C and SpO2 values were 8.69±2.41% and 95.24±3.23% respectively. P value for correlation between SpO2 and BMI was 0.3. On the other hand, p-value for correlation between SpO2 and HbA1c was 0.679 Conclusions: There was no significant effect of obesity and HbA1c on oxygen saturation in T2DM patients.